The formation of Christianity in Antioch : a social-scientific approach to the separation between Judaism and Christianity - Zetterholm, Magnus, 1958- (Routledge early church monographs., 2003)
And conclusion3 THE CULTURAL AND RELIGIOUS DIFFERENTIATION; Introduction; Constructing analytical tools; A theory of religious differentiation; Religion and value-changing processes; Muslims and religious change in modern Europe; Pluralism and religious differentiation; A theory of social integration; Variables of assimilation; The process of assimilation; The assimilation profile-a test case; The use of acculturation; Analysis-Antiochean Judaism revealed; Groups and factions; Crossing the boundaries-Antiochus the apostate; Observing torah-religious traditionalists